(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Citrus is a fruit of great importance in Brazil, mainly in the socio-economic issue as it generates employment and income due to the production and export of concentrated orange juice, as well as other products. In view of the above, this work aimed to evaluate the dormancy overcoming of citrus seeds of the cultivars: Flying Dragon, San Diego, Índio, Cravo Santa Cruz, Riverside, BRS Sunki Tropical, Volkamerian, as well as the species Poncirus trifoliata. The seeds from Embrapa (Brazilian Agricultural Research Corporation) Clima Temperado, located in Pelotas-RS, as well as from Embrapa Cassava e Fruticultura, located in Cruz das Almas-BA, were submitted to the germination test as written in the Seed Analysis Rules and a germination test in which a small cut was made in the seed coat on the side of the embryo, around 0.1 mm with the help of a stylet, which was used 200 seeds (4 samples of 50 seeds per repetition) on germitest® paper, moistened with distilled water in an amount equivalent to 2.5 times its weight and kept inside a germinator at a constant temperature of 25°C, photoperiod of 12 hours. The evaluations were carried out at the end of the 21 days after the installation of the test, providing data that were expressed in percentage of normal and abnormal seedlings and non-germinated seeds (hard, dormant or dead). of citrus seedlings at the end of the tests and the data obtained were submitted to analysis of variance and the means were compared by the Tukey test at a 5% significance level (p≤0.05), with the aid of the R- bio. It is concluded that, when evaluating germination and shoot and root length of seedlings cultivars Flying Dragon, Índio, Cravo Santa Cruz, BRS Sunki Tropical, Riverside and Volkameriano, San Diego and the species Poncirus trifoliata, were satisfactory when submitted in the dormancy breaking process, but further studies are needed.